EVALUASI PROGRAM KAMPUNG KELUARGA BERKUALITAS (KB) DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA MISKIN DI KELURAHAN PUNGGAWAN 2023 - Anoraga Sunggingprobo, Satrio; Pramono, Joko; Haryanto, Aris Tri (JI@P, 2024)
The Surakarta City government’s effort to reduce the impact of the population explosion and improve family welfare is through the Family Planning program, which is currently available in 22 sub district, one of which is Punggawan. This study purposes to describe and analyze the evaluation of the kampung keluarga berkualitas (KB) program in improving the welfare of poor families by the Surakarta City Government. The evaluation was conducted using William Dunn’s theory. The research methodology uses a qualitative approach with primary data sources obtained through in-depth interviews from various sources and secondary data through literature searches and several other documents and the technique of determining informants with purpusive sampling. The results of the study are the three programs, namely socialization, motivation and Communication Information Education on Family Planning (IEC KB) and scheduled home visits to couples of childbearing age unmetneeded, and handle stunting with JABAT handle stunting, and education on Infant and Young Child Feeding (PMBA) with food models per posyandu seen from aspects of effectiveness, effectiveness, efficiency, adequacy, responsiveness and appropriateness can be said to be good, meaning that the program is running according to plan, the budget is sufficient from the DP3AP2KB office and community self-help, but the Infant and Young Child Feeding (IYCF) education program with food models per posyandu in the aspect of responsiveness gets a burdensome response from the Punggawan community if self-handled. Keywods: Program Kampung Keluarga Berkualitas (KB), Program Evaluation with aspects of effectiveness, efficiency, adequacy, responsiveness and appropriateness